How Well Are International Branch Campuses Serving Students? - Wilkins, Stephen; Balakrishnan, Melodena (International Higher Education, 2012)
Although there is no shortage of criticisms of the international branch campus in the academic literature and professional journals, this article argues that they are fulfilling a vital role in countries all around the world, by expanding capacity and widening access to higher education. It was found that branch campuses are generally satisfying the expectations of both students and quality assurance agencies.